A STUDY ON SOFT COMPUTING AND APPLICATIONS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Soft computing is a growing set of approaches that strive to provide resilience,tractability, and cheap cost by leveraging tolerance for imprecision uncertainty and partialtruth. It may appear to be a highly appealing alternative to a totally digital system, but thereare several traps in store for researchers attempting to implement this new and intriguingtechnology. Software computing offers an appealing way to represent ambiguity in humanthought with real-world uncertainty. The main approaches of soft computing include fuzzylogic, neural networks, and evolutionary computation. Both neural networks and fuzzysystems can be utilised for nonlinear processing.